(untitled) (The Journal of Interdisciplinary Human Studies, 2025)
In this article, the theological and juridical debates that have emerged in recent centuries regarding the visitation of the blessed grave of the Prophet Muhammad (peace and blessings be upon him) are examined. Particular attention is given to the claims of certain groups who identify themselves as “Salafis,” and who, based on a literalist and incorrect interpretation of the well-known “three mosques” hadith, classify traveling with the intention of visiting the Prophet’s grave as ḥaram, bidʿah, or even a means leading to shirk. The study critically analyzes these assertions through the practice of the Companions, the established positions of the four Sunni legal schools, the sound exegetical interpretations of the relevant hadiths, and historical evidence. The findings demonstrate that, within authoritative Islamic sources, traveling for the purpose of visiting the Prophet’s grave has consistently been regarded as one of the most meritorious acts of devotion and a sacred means of attaining closeness to God.